Lessons From Italy: A Good Pension System Needs an Effective Broader Social Policy Framework - Daniele Franco; Pietro Tommasino (Intereconomics)
Abstract Italy, which is sometimes considered a laggard in terms of social and economic reforms, can boast a pension system that is, by and large, functioning sufficiently well in terms of ensuring an adequate purchasing power to retirees and a financially sustainable outlook in the long term, even when taking into account adverse demographic developments.